Efeitos da terapia de movimento induzido por restrição na funcionalidade de crianças com paralisia cerebral - Marina de Brito Brandao (2007)
The spastic hemiplegia due to cerebral palsy may lead to impairments in musculoskeletal body structures and functions and limit childs performance in activities and tasks at home, school and community contexts. The upper limb dysfunctions due to cerebral lesions often compromise the use of the affected extremity in childrens daily activities, bimanual abilities and functioning. Different approaches have been developed for this population; one of them is the constraint-induced movement therapy. This technique involves the restriction of the non-involved upper extremity, combined with an intensive training program of the affected upper extremity and the use of behavioral strategies aiming to promote the individuals participation in the intervention protocol. The objective of this study was to evaluate the effects of constraint induced movement therapy in the use of the affected extremity, bimanual abilities and functioning of children with hemiplegia, compared to children who were submitted to conventional occupational therapy. A randomized clinical trial was conducted with 16 children, from four to eight years old, with medical diagnoses of hemiplegia due to cerebral palsy. Children were recruited in a Brazilian rehabilitation centre and they were randomized into intervention or control groups. The intervention group was submitted to constraint induced movement therapy, with the use of a splint and a sling to restrain the non-affected upper extremity movements during ten hours daily. The intensive training of the affected extremity was conducted for three hours, during two weeks. After this period, the upper limb restriction was removed and children were treated three times a week, during one week, with the principles of a functional protocol to improve their performance of relevant activities. Children from control group maintained their original schedules of occupational therapy in the rehabilitation centre. All children were evaluated by a blinded examiner regarding the group of the studies with the instruments Jebsen-Taylor Hand Function (JTHF- adapted version), Child Arm Use Test (CAUT), ABILHAND-Kids Profile and Pediatric Evaluation of Disability Inventory (PEDI). Evaluations were performed in the pre-intervention, post-intervention and one month after the end of the intervention protocol (follow-up). Inferential analyses used general linear models to evaluate group, evaluation and interaction effects on score mean difference and on gain score difference, in the studys dependent variables. The significance level was established as = 0,05. When significant effects were found, pre-planned contrasts were used to find bivariate differences. Also, the number needed to treat (NNT) was calculated for functioning variables to document the clinical relevance of the intervention. The results showed higher means and gains differences in means and gains in the intervention group for the CAUT quality and willingness scales (p< 0,05) and for the PEDI functional skills and independence (p< 0,05). Furthermore, the clinical relevance of the intervention was presented in low scores of the NNT in the two functioning variables, NNT= 1,75 in functional skills and NNT= 2,33 in independence. From the results of the study, it is possible to conclude that the constraint induced movement therapy associated with the functional training promotes improvements in quality and willingness to use the affected extremity and can lead to better functioning in children with spastic hemiplegia during the performance of daily routines.